WHY IT’S TOUGH TO SNUFF THE PUFFING HABIT - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
Every year, May 31 has been designated as the ‘World No Tobacco Day’. Such a designation was made with the aim of taking preventive measures on the habit of smoking, to ensure that the habit is cut at its stem.